Explorative Versus Exploitative Business Model Change: The Cognitive Antecedents of Firm‐Level Responses to Disruptive Innovation - Osiyevskyy, Oleksiy; Dewald, Jim (Strategic Entrepreneurship Journal, 2015)
We develop a typology of incumbent adaptations to emerging disruptive business model innovations, based on two generic strategies: (1) explorative adoption of a disruptive business model; and (2) exploitative strengthening of the existing business model. We derive and test hypotheses concerning the cognitive antecedents of managerial intentions to embrace each of the two adaptation strategies. The results from our study of the real estate brokerage industry show that the explorative intentions are driven by opportunity perception, perceived performance‐reducing threat, and risk experience. Exploitative intentions are negatively associated with perceived critical threat and industry tenure and positively associated with risk experience. We contribute to the literature on disruptive business models by combining prior research into a definable framework and by testing the cognitive influences on strategic response. Copyright © 2015 Strategic Management Society.